The woman in the blue cloak - Meyer, Deon (A Benny Griessel mystery, 2019)
Early on a May morning in the depth of South Africa's winter, a woman's naked body, washed in bleach, is discovered on a stone wall beside the N2 highway at the top of Sir Lowry's Pass, some thirty-five miles from Cape Town. The local investigation stalls, so the case is referred to Captain Benny Griessel and his colorful partner Vaughn Cupido of the Hawks--the Directorate for Priority Crime Investigations. The woman proves to be Alicia Lewis, an expert in old Dutch Masters paintings specializing in the recovery of valuable lost art. Discovering the two men she had contacted before coming to South Africa reveals what she was seeking--a rare painting by Carel Fabritius, Rembrandt's finest student, not seen since it disappeared from Delft in 1654. But how Lewis died, why, and at whose hand shocks even the two veteran detectives. The Woman in the Blue Cloak is a compact jewel of a thriller, filled with Deon Meyer's earthy dialogue, clever plotting, and the memorable characters that have peopled all of Deon Meyer's award-winning novels.